A comparative study indicates both positive and purifying selection within ryanodine receptor (RyR) genes, as well as correlated evolution. Issue 3 (19th November 2013) - McKay, Patrick B.; Griswold, Cortland K.
ABSTRACT Ryanodine receptors are Ca2+ ion channels that allow Ca2+ to flow into the cytosol, from an internal store, in the form of transients. RyRs form a small gene family and vertebrates have three major isoforms, RyR1, RyR2, and RyR3, which are mixed and matched in different combinations in different tissues resulting in different Ca2+ transients for each tissue. In this study, we characterized the interspecies evolution of RyRs within vertebrates. First, we compared the nucleotide divergence of key gene regions including divergent regions (DRs), which are believed to be responsible for the functional divergence between RyRs, and mutation hot‐spot regions, which are responsible for RyR‐related pathologies. We found evidence that DRs undergo positive selection and mutation hot‐spot regions undergo purifying selection. Second, we estimated the extent of purifying selection for RyR1, RyR2, and RyR3 by estimating dN/dS ratios. We found all three genes to be under strong purifying selection, overall. This is consistent with RyRs being used in a diverse set of physiological contexts and therefore under potentially high pleiotropic constraint. Third, we tested for the correlated evolution of dN/dS ratios between RyR genes. We found that RyR2 and RyR3, and RyR3 and a skeletal form of dihydropyridine receptor (DHPR) have correlated rates of evolution. We propose that compensatory effects may explain their correlated evolution. We tested for compensatory function by simulating mutations via a physiological model of RyR function, but did not find evidence for compensation, which indicates that the correlation is likely a result of another process. J. Exp. Zool. 321A: 151–163, 2014. © 2013 Wiley Periodicals, Inc.